A closed-form solution to eye-to-hand calibration towards visual grasping. Issue 6 (20th October 2014) - Pan, Hui; Wang, Na Li; Qin, Yin Shi
Abstract : Purpose: – The purpose of this paper is to propose a method that calibrates the hand-eye relationship for eye-to-hand configuration and afterwards a rectification to improve the accuracy of general calibration. Design/methodology/approach: – The hand-eye calibration of eye-to-hand configuration is summarized as a equation AX = XB which is the same as in eye-in-hand calibration. A closed-form solution is derived. To abate the impact of noise, a rectification is conducted after the general calibration. Findings: – Simulation and actual experiments confirm that the accuracy of calibration is obviously improved. Originality/value: – Only a calibration plane is required for the hand-eye calibration. Taking the impact of noise into account, a rectification is carried out after the general calibration and, as a result, that the accuracy is obviously improved. The method can be applied in many actual applications.